Water Quality Status of Some Urban Ponds of Lucknow, Uttar Pradesh - Bhat, Mohd Muzamil; Yazdani, Taiyyaba; Narain, Kamini; Yunus, Mohammad; Shukla, Ravinder Nath (Journal of Wetlands Ecology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This study aims to investigate the physico-chemical properties of some urban ponds in the ecological system of Lucknow which is called as the city of Nawabs in U.P. But owing to the unplanned development and urbanization, the ponds of this city are struggling for their existence. Inspite of the global alarm for restoration of the water bodies, the ponds in the city are facing neglectance. For the study period ten ponds were selected. The physico-chemical parameters of the water sampled in June 2008 from ten ponds such as PH ranged from 6.55 to 7.93; Turbidity, 6.06 NTU to 8.59 NTU; Conductivity, 12.32 ms/cm to 16.84 ms/cm; D.O., 3.72 mg/l to 6.81 mg/l; B.O.D., 3.77 mg/l to 6.40 mg/l. Residual chlorine was detected only in pond A (1.09 mg/l), pond C (1.13 mg/l), pond E (1.04 mg/l) and in pond F (1.03 mg/l). Free CO2 was found between 8.7 mg/l to 19.68 mg/l. TS, TDS, and Chlorides were found much beyond the permissible levels. Alkalinity ranges between 202.55 mg/l to 310.05 mg/l; Acidity between 10.75 mg/l to 15.48 mg/l; Total Hardness between 244.49 mg/l to 254.78 mg/l. Prominent sources of pollution are the domestic sewage, kitchen flow and street runoff etc. In addition, solid waste and garbage tied in polythene bags are recorded along the banks and also floating on the water surface. Key words: Lucknow; physico-chemical; restoration; sewage; Urban ponds DOI: 10.3126/jowe.v2i1.1866 Journal of Wetlands Ecology, (2009) vol. 2, pp 67-73